Gypsies and Travellers in Housing : The Decline of Nomadism - Smith, David M.; Greenfields, Margaret (Book collections on Project MUSE., 2013)
This is the first published research from the UK to address the neglected topic of the increasing (and largely enforced) settlement of Gypsies and Travellers in conventional housing. It highlights the complex and emergent tensions and dynamics inherent when policy and popular discourse combine to frame ethnic populations within a narrative of movement.